Controllable size graphene oxide modified aerogel composite and preparation method thereof

CN118545709BActive Publication Date: 2026-10-09NINGBO GRAPHENE INNOVATION CENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410533494.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2026-10-09
Estimated Expiration
2044-04-30

AI Technical Summary

Benefits of technology

[0033] 1. The scheme of this application achieves the regulation of the thermal conductivity of the composite material by better controlling the particle size and amount of graphene oxide added; the addition of acid reagent in the preparation process is to increase the hydrolysis rate of silicon source in solvent (this involves the hydrolysis of silicon source in solvent, which is slow by nature, and acid can accelerate the hydrolysis reaction. The hydrolyzed silicon groups can rapidly condense under the catalysis of subsequent alkaline reagent, and accelerate gel nucleation and growth), while the addition of alkaline reagent is to neutralize the added acid and accelerate gel nucleation and growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118545709B_ABST
    Figure CN118545709B_ABST
Patent Text Reader

Abstract

The application discloses a controllable size graphene oxide modified aerogel composite material and a preparation method thereof. The preparation raw material of the material comprises controllable size graphene oxide, a silicon source, an alkali reagent, an acid reagent and a fiber composite material serving as a framework. The acid reagent is added in a hydrolysis stage to adjust pH to 2-5, the alkali reagent is added in a gel forming stage to adjust pH to 6-8, and the fiber composite material serving as the framework is completely immersed in a graphene oxide composite silicon wet gel precursor solution formed by the controllable size graphene oxide, the silicon source, the acid reagent and the alkali reagent, and then the graphene modified aerogel composite material is formed through gelation and drying. The scheme has the advantages that the thermal conductivity of the aerogel composite material can be reduced, and the heat insulation effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of graphene-modified aerogel composite materials, specifically to a controllable-size graphene oxide-modified aerogel composite material and its preparation method. Background Technology

[0002] With the improvement of economic, technological, and living standards, people are beginning to pursue a higher quality of life and greater safety in industrial production. To meet this development need, various thermal insulation materials have been widely discovered and applied, becoming indispensable materials. Aerogel, a lightweight porous material, has become one of the most widely used emerging materials due to its excellent thermal confinement capabilities and porosity. Aerogel has a very low thermal conductivity, effectively limiting heat transfer, and its highly porous structure provides a large specific surface area, offering more active surfaces to increase adsorption and reaction efficiency.

[0003] Compared to many traditional materials, aerogels are generally non-toxic, environmentally friendly, and have the characteristics of sustainable development.

[0004] Aerogel fiber felt is one of many aerogel materials with high application value. While traditional materials often lose their mechanical properties and thermal stability at high temperatures, it exhibits excellent thermal insulation performance and structural stability in high-temperature environments, making it widely used in thermal insulation fields. The composite of aerogel and fiber felt effectively solves the problems of poor mechanical properties and weak strength of pure aerogel. However, there is still room for improvement in the thermal conductivity of aerogel materials. Combining aerogel felt with other materials has been proven by numerous studies to be an effective approach.

[0005] Heat transfer in aerogel materials mainly includes three forms: solid-phase conduction, gas-phase conduction, and radiative conduction. Without considering the coupling effect of solid-state and gas-phase heat transfer, the thermal conductivity of aerogel is primarily the sum of the thermal conductivity of these three heat transfer mechanisms. In aerogel insulation materials, heat transfer occurs along an infinitely long path, and the contact area between particles is small, resulting in a low solid-phase thermal conductivity coefficient. From the perspective of gas-phase conduction, heat transfer occurs through collisions between gas molecules. Since the pore size of aerogel is smaller than that of gas molecules, reducing collisions between gas molecules within the aerogel is an effective way to lower the thermal conductivity of aerogel composites. Summary of the Invention

[0006] This application addresses the aforementioned shortcomings of the prior art by providing a controllable-size graphene oxide-modified aerogel composite material that can reduce the thermal conductivity of aerogel composite materials.

[0007] To solve the above-mentioned technical problems, the technical solution adopted in this application is as follows: a controllable-size graphene oxide modified aerogel composite material, the raw materials for preparing the material include: controllable-size graphene oxide, silicon source, alkaline reagent, acid reagent and fiber composite material as skeleton; the acid reagent is added during the hydrolysis stage to adjust the pH to 2-5, and the alkaline reagent is added during the gelation stage to adjust the pH to 6-8; the fiber composite material as skeleton is completely impregnated in a graphene oxide composite silicon wet gel precursor solution composed of controllable-size graphene oxide, silicon source, acid reagent and alkaline reagent, and the controllable-size graphene oxide modified aerogel composite material is formed after gelation and drying.

[0008] Furthermore, the raw material for preparing the controllable-size graphene oxide is graphite powder, and the particle size of the graphite is 300 mesh to 500 mesh.

[0009] Furthermore, the silicon source includes one or more of tetraethoxysilane, tetramethoxysilane, sodium silicate, sodium aluminum silicate, etc.

[0010] Furthermore, the alkaline reagent is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia, sodium bicarbonate, etc. (the amount added can be adjusted to the target pH range).

[0011] Furthermore, the acid reagent is one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, etc. (the amount added is sufficient to adjust the pH to the target range).

[0012] Furthermore, the fiber composite material that serves as the skeleton is one of ceramic fiber felt, glass fiber felt, aluminosilicate fiber felt, high silica fiber felt, carbon fiber felt, pre-oxidized fiber felt, alumina fiber felt, etc.

[0013] Furthermore, the specific preparation process of the controllable size graphene oxide is as follows: (1) First, the graphite powder is sieved using a sieving method to obtain graphite powder raw material whose particle size meets the requirement of being able to pass through a 300-mesh sieve but not a 500-mesh sieve; (2) The sieved graphite powder raw material and concentrated sulfuric acid are stirred in an ice bath, and then potassium permanganate is slowly added while maintaining the temperature of the reaction system at 0-10℃ during the addition process. Then, the reaction mixture is transferred to an oil bath at 30-45℃ and stirred for 0.5-2 hours, and then stirred at 80-95℃ for 20-40 minutes. Then, the reaction mixture is cooled to 35-42℃ and stirred for 0.5-1.5 hours to obtain a reaction mixture containing graphene oxide with controlled particle size; (3) The reaction mixture is filtered and washed with a hydrochloric acid aqueous solution at a volume ratio of 1:(9-12) to remove metal ions, and then deionized water is added to obtain graphene oxide with different solution concentrations, or the graphene oxide powder is obtained by freeze drying.

[0014] Furthermore, the sieving method in step (1) of the preparation of controllable-size graphene oxide is not limited.

[0015] This application also provides a method for preparing the above-mentioned controllable-size graphene oxide modified aerogel composite material, the specific preparation steps of which include:

[0016] (1) Preparation of graphene oxide modified wet gel precursor solution: The prepared controllable size graphene oxide, silicon source, alcohol, water, acid reagent and base reagent are mixed in proportion and addition order to prepare graphene oxide modified wet gel precursor solution, wherein the molar ratio of silicon source: alcohol: water is 1:(1~50):(1~25).

[0017] (2) Impregnation: The fiber composite material that serves as the skeleton is impregnated in the graphene oxide modified wet gel precursor liquid prepared in step (2) and then removed to obtain the graphene modified sol composite material.

[0018] (3) Gel: The graphene-modified sol composite material prepared in step (2) is heated to 40° to 60° and gel reaction is carried out at this temperature for 1 to 5 hours. Then, the solvent is replaced with alcohol 2 to 5 times to remove impurities.

[0019] (4) Drying: The graphene oxide modified wet gel composite material obtained in step (3) after removing impurities is dried to obtain a graphene oxide modified aerogel composite material with controllable size.

[0020] Furthermore, the preparation method of controllable-size graphene oxide in step (1) is not limited to the improved Hummers method, but the Hummers method is also within the selection range.

[0021] Furthermore, in step (1), the acid reagent is added at the following time: after the controllable-size graphene oxide, silicon source, alcohol, and water are fully mixed, the amount added is to adjust the pH of the reaction system to 2-5, after thorough stirring, and then the alkali reagent is added to adjust the pH of the reaction system to 6-8.

[0022] Furthermore, the mass of the controllable-size graphene oxide added in step (1) is 0.5%-8% (here, the mass fraction of controllable-size graphene oxide added is the mass fraction of the graphene oxide composite silica sol; here, the graphene oxide composite silica sol is obtained by mixing silicon source, anhydrous ethanol, water, controllable-size graphene oxide and hydrolysate (acid reagent).

[0023] Furthermore, the silicon source mentioned in step (1) is one or more of tetraethoxysilane, tetramethoxysilane, sodium silicate, sodium aluminum silicate, etc.

[0024] Furthermore, the controllable-size graphene oxide mentioned in step (1) can be in powder or slurry form.

[0025] Furthermore, the acid reagent mentioned in step (1) is one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, etc. (the amount added is enough to adjust the pH to the target range).

[0026] Furthermore, the alkaline reagent mentioned in step (1) is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia, sodium bicarbonate, etc. (the amount added is enough to adjust the pH to the target range).

[0027] Furthermore, the composite material that serves as the skeleton in step (2) is one of ceramic fiber felt, glass fiber felt, aluminosilicate fiber felt, high silica fiber felt, carbon fiber felt, pre-oxidized fiber felt, and alumina fiber felt.

[0028] Furthermore, the soaking time described in step (2) is 5-25 hours.

[0029] Furthermore, after the gel removal treatment for impurity ions described in step (3), the graphene oxide modified wet gel composite material is aged at 30-55°C for 8-40 hours. The use of the above steps can improve the mechanical properties, thermal stability and weather resistance of the material, and increase its service life.

[0030] Furthermore, the alcohol mentioned in steps (1) and (3) is one of anhydrous ethanol and anhydrous propanol.

[0031] Furthermore, the drying process described in step (4) is one of supercritical drying, freeze drying, or atmospheric pressure drying.

[0032] The advantages and beneficial effects of this application are as follows:

[0033] 1. The scheme of this application achieves the regulation of the thermal conductivity of the composite material by better controlling the particle size and amount of graphene oxide added; the addition of acid reagent in the preparation process is to increase the hydrolysis rate of silicon source in solvent (this involves the hydrolysis of silicon source in solvent, which is slow by nature, and acid can accelerate the hydrolysis reaction. The hydrolyzed silicon groups can rapidly condense under the catalysis of subsequent alkaline reagent, and accelerate gel nucleation and growth), while the addition of alkaline reagent is to neutralize the added acid and accelerate gel nucleation and growth.

[0034] 2. This application uses controllable-size graphene oxide as a modifying additive for aerogel materials. Graphene oxide with a controllable size range is prepared using a graded sieving method and a modified Hummers method. Based on the principle of heat transfer limitation in aerogel materials, by adding graphene oxide of appropriate size and dosage range, the presence of graphene oxide nanosheets (the graphene oxide nanosheets obtained in this application are sheet-like and controllable in size) can reduce effective collisions between gas molecules. This is because the graphene oxide nanosheets can block the heat transfer channels, preventing heat from passing directly and hindering heat transfer. This process effectively reduces the thermal conductivity of aerogel materials. Simultaneously, the abundant oxygen-containing functional groups such as hydroxyl and carboxyl groups on the surface of graphene oxide can tightly bind with the silicon-containing intermediates in the sol, preventing the graphene oxide from detaching as powder after molding. The composite sol binds to materials such as ceramic fiber mat, glass fiber mat, aluminosilicate fiber mat, high-silica fiber mat, carbon fiber mat, pre-oxidized fiber mat, and alumina fiber mat, which serve as the framework. The resulting aerogel, after drying, significantly improves its mechanical properties and stability, thus achieving the desired thermal conductivity.

[0035] 3. The technical solution of this application uses various fiber felt materials as the overall skeleton to provide good structural stability and strength. The fiber felt material can support and maintain the shape of the aerogel, preventing it from deforming or disintegrating; at the same time, the fiber felt material has softness and plasticity, adapting to various shape and size requirements, making aerogel composite materials easier to apply in various complex structures and devices; the material has good processability, and can be sheared, cut, and molded to meet the needs of different shapes and sizes; therefore, the graphene oxide modified aerogel composite fiber felt prepared using the specific scheme of this application has the characteristics of good heat resistance and insulation, and can effectively improve the shortcomings of pure silicon-based aerogel such as poor structural stability, fragility, and difficulty in processing; the process is simple and convenient to operate, and it is expected to expand the application range of aerogel composite materials in high-temperature fields; the prepared controllable-size graphene oxide modified aerogel composite fiber felt not only has low thermal conductivity, but also has good stability under high-temperature conditions, and has broad prospects for heat insulation applications. Attached Figure Description

[0036] Figure 1 This is a flowchart illustrating the preparation process of the controllable-size graphene oxide-modified aerogel composite material of this application.

[0037] Figure 2 The contact angle diagram (left) of the controllable-size graphene oxide modified aerogel composite material of this application is compared with the contact angle diagram of commercially available aerogels (right). Detailed Implementation

[0038] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are merely preferred embodiments, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this invention.

[0039] The preparation of the controllable graphene oxide modified aerogel composite material in this application can be referred to Figure 1 The flowchart shown is shown; however, the specific detailed embodiments are described below:

[0040] Example 1:

[0041] The controllable-size graphene oxide modified aerogel composite material of this embodiment is prepared mainly from the following raw materials: controllable-size graphene oxide, tetraethyl orthosilicate as the silicon source, sulfuric acid as the acid reagent, sodium hydroxide as the alkali reagent, anhydrous ethanol, water, and fiber composite material as the skeleton; wherein the molar ratio of silicon source, anhydrous ethanol, and water is 1:15:8; the amount of controllable-size graphene oxide added is 1% of the graphene oxide composite silica sol, the amount of acid reagent added is to adjust the pH of the reaction system to 3-4, and the amount of alkali reagent added is to adjust the pH of the reaction system to 6-7; the fiber composite material as the skeleton is simply impregnated with the graphene oxide modified wet gel precursor solution.

[0042] (1) Preparation of controllable-size graphene oxide: The size of the prepared graphene oxide is controlled by a modified Hummer method combined with a graded sieving method. First, natural graphite powder is ground using a pulverizer, and the raw material that can pass through a 300-mesh sieve but not a 500-mesh sieve is collected and sieved. The sieved graphite powder (1g) and concentrated sulfuric acid (30ml industrial grade) are mechanically stirred (150rpm / min) in an ice bath (less than 10℃). Then, potassium permanganate (3g) is slowly added while keeping the temperature of the reaction system below 10℃ during the addition process. After the addition is completed, the reaction system is transferred to an oil bath at 40℃ and stirred for 1 hour. Then, it is stirred at 95℃ for 30 minutes. The reaction mixture is then cooled to 40℃ and stirred for another hour to obtain a reaction mixture containing graphene oxide with controlled particle size. The reaction mixture is filtered and washed three times with a 1:10 volume ratio hydrochloric acid aqueous solution to remove metal ions, resulting in a controllable-size graphene oxide filter cake. The controllable-size graphene oxide powder is obtained by freeze-drying.

[0043] (2) Preparation of graphene oxide modified silica sol: Using the obtained controllable-size graphene oxide as a modifier, tetraethyl orthosilicate as a silicon source, and sulfuric acid as a hydrolysant (acid reagent), the silicon source, anhydrous ethanol, and water were mixed and dispersed in the following molar ratio = 1:15:8. Then, 1% by mass of controllable-size graphene oxide was added, and sodium hydroxide was added as a hydrolysant to adjust the pH of the reaction system to 3-4. A homogeneous graphene oxide composite silica sol was obtained by mixing the silicon source, anhydrous ethanol, water, controllable-size graphene oxide, and hydrolysant (acid reagent). The "1% by mass of controllable-size graphene oxide" refers to the percentage by mass of controllable-size graphene oxide in the total "graphene oxide composite silica sol".

[0044] (3) Preparation of graphene oxide modified wet gel precursor solution: Add coagulant alkali (sodium hydroxide, i.e. alkali reagent) to the graphene oxide composite silica sol obtained in step (2), the amount of which is adjusted to the pH of the reaction system to 6-7, and stir evenly to obtain graphene oxide modified wet gel precursor solution.

[0045] (4) Preparation of graphene oxide modified wet gel composite material: Select a molding container, transfer the obtained graphene oxide modified wet gel precursor liquid into the container, and then fully immerse the ceramic fiber felt in the precursor liquid (maintain for 24 hours), seal and heat to 60° to gel to obtain graphene oxide modified wet gel felt, and then use anhydrous ethanol to replace the solvent 3 times (that is, soak the wet gel felt in anhydrous ethanol for replacement, each soaking for 8 hours for replacement) to replace the sulfate, sodium ions, water and other components in the wet gel felt to obtain graphene oxide modified wet gel composite material.

[0046] (4) Preparation of controllable size graphene oxide modified aerogel composite material: supercritical drying of graphene oxide modified wet gel composite material to obtain controllable size graphene oxide modified composite aerogel felt (aerogel composite material).

[0047] Example 2:

[0048] The controllable-size graphene oxide modified aerogel composite material of this embodiment is prepared mainly from the following raw materials: controllable-size graphene oxide, tetraethyl orthosilicate as the silicon source, sulfuric acid as the acid reagent, sodium hydroxide as the alkali reagent, anhydrous ethanol, water, and fiber composite material as the skeleton; wherein the molar ratio of silicon source, anhydrous ethanol, and water is 1:15:8; the amount of controllable-size graphene oxide added is 5% of the graphene oxide composite silica sol, the amount of acid reagent added is to adjust the pH of the reaction system to 3-4, and the amount of alkali reagent added is to adjust the pH of the reaction system to 6-7; the fiber composite material as the skeleton is simply impregnated with the graphene oxide modified wet gel precursor solution.

[0049] Controllable-size graphene oxide was prepared using the method described in Example 1;

[0050] The preparation method of controllable-size graphene oxide modified composite aerogel materials, and the specific implementation steps are as follows:

[0051] (1) Preparation of graphene oxide modified silica sol: Using controllable size graphene oxide as a modifier, nitric acid as a hydrolysant, and methyl orthosilicate as a silicon source, the silicon source, anhydrous ethanol and water were mixed and dispersed in the following molar ratio = 1:15:8. 5% by mass of controllable size graphene oxide was added, and the pH was adjusted to 3-4 by adding the hydrolysant to obtain a uniformly mixed graphene oxide modified silica sol.

[0052] (2) Preparation of graphene oxide modified wet gel precursor solution: Add coagulant (alkali reagent) ammonia water to the graphene oxide modified silica sol prepared in step (1), adjust the pH to 6-7, and stir evenly to obtain graphene oxide modified wet gel precursor solution.

[0053] (3) Preparation of graphene oxide modified wet gel composite material: Select a molding container, transfer the obtained graphene oxide modified wet gel precursor liquid into the container, and then fully immerse the glass fiber mat in the precursor liquid (maintain for 12 hours), seal and heat to 55°C until gelation to obtain graphene oxide modified composite wet gel mat. Perform hydrophobic treatment by immersing in anhydrous ethanol: methyltriethoxysilane = 3:1 hydrophobic treatment solution for 15 hours, and then use anhydrous ethanol to replace the solvent 3 times (that is, soak the composite wet gel mat in anhydrous ethanol for replacement, each time soaking for 8 hours for replacement) to replace the nitrate, ammonium ions, water and other components in the composite wet gel mat; then place the replaced wet gel mat at 50°C for aging and maintain for 34 hours to obtain graphene oxide composite wet gel mat (graphene oxide modified wet gel composite material).

[0054] (4) Preparation of controllable size graphene oxide modified aerogel composite material: The graphene oxide composite wet gel felt obtained after aging in step (3) is subjected to supercritical drying to obtain controllable size graphene modified composite aerogel felt (aerogel composite material).

[0055] Example 3:

[0056] The controllable-size graphene oxide modified aerogel composite material of this embodiment is prepared mainly from the following raw materials: controllable-size graphene oxide, tetraethyl orthosilicate as the silicon source, sulfuric acid as the acid reagent, sodium hydroxide as the alkali reagent, anhydrous ethanol, water, and fiber composite material as the skeleton; wherein the molar ratio of silicon source, anhydrous ethanol, and water is 1:15:8; the amount of controllable-size graphene oxide added is 5% of the graphene oxide composite silica sol, the amount of acid reagent added is to adjust the pH of the reaction system to 3-4, and the amount of alkali reagent added is to adjust the pH of the reaction system to 6-7; the fiber composite material as the skeleton is simply impregnated with the graphene oxide modified wet gel precursor solution.

[0057] Controllable-size graphene oxide was prepared using the method described in Example 1;

[0058] The preparation method of controllable-size graphene oxide modified composite aerogel materials, and the specific implementation steps are as follows:

[0059] (1) Preparation of graphene oxide modified silica sol: Using the obtained controllable size graphene oxide as a modifier, tetraethyl orthosilicate as a silicon source, and sulfuric acid as a hydrolysant (acid reagent), the silicon source, anhydrous ethanol and water are mixed and dispersed in the following molar ratio = 1:15:8, and then 2% by mass of controllable size graphene oxide is added, and the pH is adjusted to 3-4 by adding hydrolysant, and a uniform graphene oxide composite silica sol is obtained by mixing.

[0060] (2) Preparation of graphene oxide modified wet gel precursor solution: Add coagulant alkali (sodium hydroxide, i.e. alkali reagent) to the graphene oxide composite silica sol obtained in step (2), the amount of which is adjusted to the pH of the reaction system to 6-7, and stir evenly to obtain graphene oxide modified wet gel precursor solution.

[0061] (3) Preparation of graphene oxide modified wet gel composite material: Select a molding container, transfer the obtained graphene oxide modified wet gel precursor liquid into the container, and then fully immerse the ceramic fiber felt in the precursor liquid (maintain for 24 hours), seal and heat to 60° to gelation to obtain graphene oxide modified wet gel felt, and perform hydrophobic treatment by immersing in anhydrous ethanol: methyltriethoxysilane = 3:1 for 14 hours, and then use anhydrous ethanol to replace the solvent 3 times (that is, immerse the wet gel felt in anhydrous ethanol for replacement, each time for 8 hours) to replace the sulfate, sodium ion, water and other components in the wet gel felt to obtain graphene oxide modified wet gel composite material.

[0062] (4) Preparation of controllable-size graphene oxide-modified aerogel composite material: The graphene oxide-modified wet aerogel composite material was subjected to supercritical drying to obtain controllable-size graphene oxide-modified composite aerogel felt (aerogel composite material). Comparative Example 1:

[0063] The difference from Example 1 is that the amount of modified graphene oxide added is 10% of the mass fraction of the silica sol.

[0064] Comparative Example 2:

[0065] Comparative Example 2 is a common aerogel felt material on the market.

[0066] Comparative Example 3:

[0067] The difference from Example 1 is that natural graphite powder raw materials that can pass through a 100-mesh sieve but not a 200-mesh sieve are collected for modification.

[0068] Comparative Example 4:

[0069] The difference from Example 1 is that natural graphite raw materials that can pass through a 500-mesh sieve but not a 1000-mesh sieve are collected for modification.

[0070] Table 1. Hydrophobic and thermal conductivity properties of the aerogel composite fiber materials prepared in the examples and comparative examples.

[0071]

[0072] The performance comparison of various aerogel felts in Examples 1-2 and Comparative Examples 1-4 shows that the controlled-size graphene oxide-modified aerogel composite material with a reasonable formulation in this application has a significantly lower thermal conductivity compared to ordinary silicone aerogel felt composite fiber materials on the market. At room temperature, the ideal thermal conductivity of the composite material prepared by this application can be no greater than 0.023 W / m·K, meeting the current requirements for materials used in thermal insulation. However, the amount and size of graphene oxide added need to be within a reasonable range; otherwise, it will not only increase the thermal conductivity of the material but may also affect the hydrophobicity of the aerogel material (a smaller water contact angle indicates lower hydrophobicity and stronger hydrophilicity). This application's technical solution is the first to improve the thermal conductivity of aerogel felts from the perspectives of graphene oxide particle size control and addition amount, providing a reference for improving the thermal insulation performance of this type of aerogel felt material. (See attached...) Figure 2 The image shows a comparison (right) between the contact angle diagram of the controllable-size graphene oxide modified aerogel composite material prepared in Example 2 of this application (left) and the contact angle diagram of a commercially available aerogel (Comparative Example 2). The test results show that although the contact angle is reduced after coating with a thin layer of graphene oxide, it still has good surface hydrophobicity.

Claims

1. A controllable-size graphene oxide-modified aerogel composite material, characterized in that: The raw materials for preparing this material include: controllable-size graphene oxide, silicon source, alkaline reagent, acid reagent, and fiber composite material serving as the skeleton; the acid reagent is added during the hydrolysis stage to adjust the pH to 2-5, and the alkaline reagent is added during the gelation stage to adjust the pH to 6-8; the fiber composite material serving as the skeleton is completely impregnated in the graphene oxide composite silicon wet gel precursor solution composed of controllable-size graphene oxide, silicon source, acid reagent, and alkaline reagent, and after gelation and drying, a graphene-modified aerogel composite material is formed; the specific preparation process of the controllable-size graphene oxide is as follows: (1) First, the graphite powder is sieved using a sieving method to obtain graphite powder raw materials whose particle size meets the requirement of being able to pass through a 300-mesh sieve but not a 500-mesh sieve; (2) The sieved graphite powder raw materials and concentrated sulfuric acid are stirred in an ice bath, and then slowly Add potassium permanganate and keep the temperature of the reaction system at 0-10°C during the addition process. Then transfer the reaction mixture to an oil bath at 30-45°C and stir for 0.5-2 hours. Then stir at 80-95°C for 20-40 minutes. Then lower the reaction mixture to 35-42°C and stir for 0.5-1.5 hours to obtain a reaction mixture containing graphene oxide with controlled particle size. (3) Filter and wash the reaction mixture with a hydrochloric acid aqueous solution at a volume ratio of 1:(9-12) to remove metal ions. Then add deionized water to obtain graphene oxide with different solution concentrations, or freeze-dry to obtain graphene oxide powder. The process also includes the step of preparing graphene oxide composite silica sol, wherein the amount of controllable size graphene oxide added in the preparation accounts for 1%-5% of the total mass of graphene oxide composite silica sol.

2. The controllable-size graphene oxide-modified aerogel composite material according to claim 1, characterized in that: The silicon source is one or more of tetraethoxysilane, tetramethoxysilane, sodium silicate, and sodium aluminum silicate.

3. The controllable-size graphene oxide-modified aerogel composite material according to claim 1, characterized in that: The acid reagent is one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, and acetic acid.

4. The controllable-size graphene oxide-modified aerogel composite material according to claim 1, characterized in that: The alkaline reagent is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia, and sodium bicarbonate.

5. The controllable-size graphene oxide-modified aerogel composite material according to claim 1, characterized in that: The fiber composite material that serves as the skeleton is one of ceramic fiber felt, glass fiber felt, aluminosilicate fiber felt, high silica fiber felt, carbon fiber felt, pre-oxidized fiber felt, and alumina fiber felt.

6. A method for preparing a controllable-size graphene oxide-modified aerogel composite material according to any one of claims 1-5, characterized in that: The preparation steps include: (1) Preparation of graphene oxide composite silicon wet gel precursor solution: The prepared controllable size graphene oxide, silicon source, alcohol, water, acid reagent and base reagent are mixed in proportion and addition order to prepare graphene oxide composite silicon wet gel precursor solution, wherein the molar ratio of silicon source: alcohol: water is 1:(1~50):(1~25). (2) Impregnation: The fiber composite material that serves as the skeleton is impregnated in the graphene oxide composite silicon wet gel precursor liquid prepared in step (2), and then taken out to obtain the modified graphene oxide sol composite material. (3) Gel: The modified graphene oxide sol composite material prepared in step (2) is heated to 40-60°C and a gel reaction is carried out at this temperature for 1-5 hours to obtain the graphene oxide modified wet gel composite material. The solvent is replaced with alcohol 2-5 times to remove impurity ions. (4) Drying: The graphene oxide modified wet gel composite material obtained in step (3) is dried to obtain a graphene oxide modified aerogel composite material with controllable size.

7. The method for preparing the controllable-size graphene oxide modified aerogel composite material according to claim 6, characterized in that: In step (1), the acid reagent is added after the modified graphene oxide, silicon source, alcohol and water are fully mixed, and the amount added is to adjust the pH of the reaction system to 2-5; after thorough stirring, the alkali reagent is added to adjust the pH of the reaction system to 6-8.

8. The method for preparing the controllable-size graphene oxide modified aerogel composite material according to claim 6, characterized in that: The silicon source mentioned in step (1) is one or more of tetraethoxysilane, tetramethoxysilane, sodium silicate, and sodium aluminum silicate; the acid reagent is one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, and acetic acid; the alkaline reagent is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia, and sodium bicarbonate; the composite material acting as the skeleton is one of ceramic fiber felt, glass fiber felt, aluminum silicate fiber felt, high silica fiber felt, carbon fiber felt, pre-oxidized fiber felt, and alumina fiber felt; and the alcohol is one of anhydrous ethanol and anhydrous propanol.

9. The method for preparing the controllable-size graphene oxide modified aerogel composite material according to claim 8, characterized in that: The controllable-size graphene oxide mentioned in step (1) is in powder or slurry form; the impregnation time mentioned in step (2) is 5-25 hours.

10. The method for preparing the controllable-size graphene oxide modified aerogel composite material according to claim 6, characterized in that: After removing impurities from the gel as described in step (3), the process also includes aging the graphene-modified silica composite wet gel material at 30–55°C for 8–40 hours.

11. The method for preparing the controllable-size graphene oxide modified aerogel composite material according to claim 6, characterized in that: The drying process described in step (4) is one of supercritical drying, freeze drying, or atmospheric pressure drying.

Citation Information

Patent Citations

  • Less-lamella graphene oxide dispersion liquid and preparation method thereof

    CN110606481A

  • Preparation method of graphene composite silica aerogel thermal insulation material

    CN112876195A